Introduction to communication research - Reinard, John C. (Madison, Wis. : Brown & Benchmark, 1994)
"This book represents the product of many years of experimentation with instruction of the introductory research methods. In fact, for years "underground" copies of the materials in this book and related resources were used to teach highly successful classes at nearly a dozen Western universities."
Includes bibliographical references (p. 340-348) and indexes.
English text.
Keywords: Communication -- Research -- Methodology